Development of Human Skeleton Comic to Enchance Student’s Motivation and Science Learning Outcomes - Burhanudin, Fahreza; Endang Susilowati, Sri Mulyani; Haryani, Sri (Journal of Primary Education, 2019)
The purpose of this study was to produce teaching material for human skeleton material in 5th grade class Elementary School Mahad Islam. The research used research and development models (R&D) with ten stages, i.e. (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revisions, (6) product trials, (7) product revisions, (8) usage trials, (9) final products, (10) dissemination. Comic are declared valid by obtaining scores from media experts, namely 4.0 with good categories and obtaining scores from material experts, namely 3.91 including good categories. Comic are declared effective by obtaining a score of learning interest that is 86% including in the high category. N-Gain measurements show a result of 6.7 including medium category. Learning outcomes of students classical completeness has a percentage of 90.9% already above 80% requirement. Based on the results of the research, it can be concluded that the comic material with the material of human skeleton in science subjects is valid and effective so that it is suitable to be used as teaching material. In this study, comic teaching materials has the benefit that are creative, innovative and fun for students.